6=3h+3

Simple and best practice solution for 6=3h+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=3h+3 equation:


Simplifying
6 = 3h + 3

Reorder the terms:
6 = 3 + 3h

Solving
6 = 3 + 3h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-3h' to each side of the equation.
6 + -3h = 3 + 3h + -3h

Combine like terms: 3h + -3h = 0
6 + -3h = 3 + 0
6 + -3h = 3

Add '-6' to each side of the equation.
6 + -6 + -3h = 3 + -6

Combine like terms: 6 + -6 = 0
0 + -3h = 3 + -6
-3h = 3 + -6

Combine like terms: 3 + -6 = -3
-3h = -3

Divide each side by '-3'.
h = 1

Simplifying
h = 1

See similar equations:

| y=500x+25 | | y=-10x+130x-400 | | 1x-4=2x+2 | | 4 = t2+ 2 | | x(-2x-13)=-1 | | 2p+-2=-4 | | 18+(3x+5)=5(x-1)-6 | | 5x-10=4x+6 | | 2m-t=5m+5 | | 4-X=2X-3X+1 | | 130=-5(3x-5) | | 7x+9=49x^2+126x+81 | | 5X+X=6X+3 | | 2x-y+6z=20 | | x+7-2=3x | | 4-6x+8=1-5x-4 | | 8=3h+5 | | (0-k)(1-k)=0 | | 2x^2+10+52=0 | | (X+3)+2(X-4)=5(X+3) | | (0-k)(0-k)=0 | | X+2x+2x-30=140 | | 9(x+8)+12=8(x+18)+10 | | Y=-3x*2 | | Y=4x^2+3x | | 2=2x-6x+3x+9 | | 360-65-x=44 | | q=40+-0.5p | | 3+4(2x+5)=39 | | 48/6= | | x^2+30x-40=0 | | 5x+5=52 |

Equations solver categories